Effect of Hydrothermal Pretreatment on Anaerobic Digestion of Erythromycin Fermentation Dregs: Biogas Production, Antibiotic Resistance Gene Evolution, and Microbial Community Dynamics - Wang, Yafei; Kuang, Shaoping; Wang, Mengmeng (Frontiers in Environmental Science, 2022)
The utilization of erythromycin fermentation dregs (EFD), one kind of solid biowaste, was limited due to the high-level residue of antibiotics. Hydrothermal pretreatment (HT) was of great potential to remove residual antibiotics, however, its harmless performance and influence on EFD anaerobic digestion (AD) process remain unclear. In this study, HT was conducted for erythromycin removal before EFD AD with the temperature ranging from 80 to 180 ℃. Moreover, change of biogas yield, antibiotic resistance genes (ARGs), and microbial community in the EFD AD process were compared among different treatments. The results showed that under the optimal hydrothermal temperature of 160 ℃, more than 85% of erythromycin was eliminated. In addition, HT significantly reduced the ARGs in the EFD AD process, ermT and mefA relative abundance decreased by one order of magnitude. Mobile genetic elements (IntI1 and Tn916/1545) also showed decrease tendency with the hydrothermal temperature elevating. The maximum methane production of 428.3 mL·g-1 VS was obtained in AD system of EFD with hydrothermal treated at 160 ℃. It is attributed to the cooperation of hydrolysis and acidogenesis bacteria (e.g. Aminicenantales and Sedimentibacter) and methylotrophic methanogens (Candidatus_Methanofastidiosum and Methanosarcina), and they presented the highest relative abundance in this group. The results indicated methylated substances reduction was the major methanogenesis route. Hydrothermal technology was of great potential to realize the harmless treatment of EFD and for recycling EFD via AD.